2017
DOI: 10.3389/fphar.2017.00773
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal, Histopathological Efficacy of Penicillium daleae against Larvae of Culex quinquefasciatus and Aedes aegypti Plus Biotoxicity on Artemia nauplii a Non-target Aquatic Organism

Abstract: Mosquitoes can transmit the terrible diseases to human beings. Soil-borne fungal products act as potential source for low-cost chemicals, used for developing ecofriendly control agents against mosquito-vector borne diseases. The prime aim of study was to check the larvicidal potential of fungus mycelia (by ethyl acetate solvent) extract from Penicillium daleae (KX387370) against Culex quinquefasciatus and Aedes aegypti and to test the toxicity of brine shrimp Artemia nauplii, by observing the physiological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 77 publications
2
27
0
Order By: Relevance
“…Many histological changes in most insects due to the infection with different entomopathogenic fungi were revealed using light and electron microscopy by many investigators (Scheneider et al, 2013;Gabarty et al, 2014;Khaleil et al, 2016;Ragavendran et al, 2017). The insects cuticle, with its underlying epidermis, forms the integument.…”
Section: Results Of Histological Studymentioning
confidence: 99%
“…Many histological changes in most insects due to the infection with different entomopathogenic fungi were revealed using light and electron microscopy by many investigators (Scheneider et al, 2013;Gabarty et al, 2014;Khaleil et al, 2016;Ragavendran et al, 2017). The insects cuticle, with its underlying epidermis, forms the integument.…”
Section: Results Of Histological Studymentioning
confidence: 99%
“…quinquefasciatus. Recently, Ragavendran et al (2017) reported that the midgut cells of Ae. aegypti (fourth-instar larvae) had swelling in the gut lumen, reducing intercellular contacts and degeneration of nuclei, after treated with P. daleae mycelium extract.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation reveals that the uptake with A. terreus mycelium ethyl acetate extract treated with A. nauplii shown an accumulation of toxin in the mid-gut region leads to the brine shrimp death. Recently, Ragavendran et al (2017) identified Penicillium daleae mycelia metabolites and tested for A. nauplii alterations of body structures and loss of antenna with the LC 50 and LC 90 value 0.290 and 0.609 μg/ml, respectively. Similarly, Ruhul Amin et al (2003) reported the LC 50 value (17.78 μg/ml) of Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations